1995
DOI: 10.1016/s0022-5347(01)66823-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Adjustment of Children and Adolescents After Different Types of Hypospadias Surgery: A Norm-related Study

Abstract: In addition to procedures that bring the meatus to a more terminal position, those that bring it more ventral can be performed without negatively affecting psychosexual adjustment. Hypospadias patients were reluctant to seek advice for problems and, therefore, they should be followed through adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 17 publications
10
87
2
5
Order By: Relevance
“…Previous publications suggest that psychosexual function and quality of life in patients with distal hypospadias may be impaired 1,2 . However it is not clear, which factors influence this outcome and to which extent the surgical result contributes to it.…”
Section: Introductionmentioning
confidence: 97%
“…Previous publications suggest that psychosexual function and quality of life in patients with distal hypospadias may be impaired 1,2 . However it is not clear, which factors influence this outcome and to which extent the surgical result contributes to it.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have demonstrated, that boys with hypospadias suffer from negative genital appraisal and sexual inhibitions and that self-reported health related quality of life (HRQoL) can be diminished (3)(4)(5). There is a general agreement, that at certain ages, a child may be more vulnerable to psychological distress related to surgery (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition, significant contradiction exists in the literature regarding the psychosexual impact of hypospadias and hypospadias repair. [3][4][5] Some studies report that sexual development and function are normal, [6][7][8] whereas others report less positive results. [9][10][11] Some investigators have reported that all patients are satisfied with the cosmetic result, 12 whereas others have found that 38% still felt deformed 11 or that as many as 72% regarded their penis as abnormal.…”
mentioning
confidence: 99%
“…6 Regardless of their bias, most authors agree that these patients need to be followed into adolescence and adulthood to assess patient satisfaction. [4][5][6]11,13,14 To our knowledge, there is no Canadian-based literature on this subject, and there are few studies in the world literature that focus on functional outcomes and patient satisfaction as those with hypospadias grow into adulthood. 6,11,14,15 This study aimed to address these deficiencies in current understanding of the long-term outcomes of hypospadias repair during childhood.…”
mentioning
confidence: 99%